Foraging strategy and tree structure as drivers of arboreality and suspensory behaviour in savannah-dwelling chimpanzees - Drummond-Clarke, Rhianna C.; Reuben, Susan Chege; Stewart, Fiona A.; Piel, Alex K.; Kivell, Tracy L. (Frontiers in Ecology and Evolution, 2025)
IntroductionThe association between an open habitat (e.g., savannah-mosaics) and increased terrestriality is central to hypotheses of hominin evolution, especially the emergence and evolution of bipedalism, as well as ape evolution as far back as the early Miocene. However, the selective pressures that act on apes in an open habitat remain poorly understood. Observations of chimpanzees that live in savannah-mosaics, analogous to some reconstructed hominoid palaeohabitats, can provide valuable insight into the behavioural adaptations of a large-bodied, semi-arboreal ape to an open habitat, characterised by sparsely distributed food sources and a broken canopy. We previously showed that savannah-dwelling chimpanzees in the Issa Valley, western Tanzania, maintain a high level of arboreality, and particularly suspensory behaviour, largely associated with foraging. Here, we investigate how chimpanzee foraging strategy in a savannah-mosaic may drive a high frequency of arboreal behaviours despite reduced arboreal pathways. Specifically, we hypothesized that Issa chimpanzees would spend more time foraging (and moving) per tree to maximize utilization of food in a sparse landscape. This foraging strategy would be facilitated by foraging in trees with large crowns and abundant terminal-branch foods, which are characteristic of miombo woodlands. However, the link between foraging positional behaviour and tree structure remains understudied.MethodsWe collected data on arboreal foraging behaviour and corresponding tree structural characteristics over five months in the dry season, and used generalized linear mixed models to test for any effect of food type and tree structural characteristics on (1) duration of foraging bouts, (2) frequency of locomotion, and (3) use of suspensory behaviour.ResultsWe found that food types and tree structures found in woodland vegetation are associated with more time spent in foraging trees, a higher rate of locomotion, and the use of suspension in particular.DiscussionOur results suggest that arboreal, and especially suspensory, locomotion can be advantageous for foraging in a savannah-mosaic and not just closed forest habitats. These findings have implications for reconstructing hominoid positional behaviour from the fossil record and provide a model for how arboreality, and specifically suspensory behaviour, could have been an important part of the hominoid niche in savannah-mosaic habitats.